2009
DOI: 10.1002/ajim.20704
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal injuries resulting from patient handling tasks among hospital workers

Abstract: The use of mechanical lift equipment could significantly reduce the risk of some patient handling injuries but additional interventions need to be considered that address other patient handling tasks. Smaller high-risk workgroups should not be neglected in prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 23 publications
4
108
0
1
Order By: Relevance
“…Each year, more than 10,000 nurses in the United States experience work-related musculoskeletal disorders resulting in lost work days and nurses rank among the top five occupations for musculoskeletal disorders (Bureau of Labor Statistics, 2010). Injuries from patient handling tasks account for 31-66% of all musculoskeletal injuries among healthcare workers (D'Arcy et al, 2012;Kim et al, 2012;Pompeii et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Each year, more than 10,000 nurses in the United States experience work-related musculoskeletal disorders resulting in lost work days and nurses rank among the top five occupations for musculoskeletal disorders (Bureau of Labor Statistics, 2010). Injuries from patient handling tasks account for 31-66% of all musculoskeletal injuries among healthcare workers (D'Arcy et al, 2012;Kim et al, 2012;Pompeii et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of work-related musculoskeletal (MS) injuries is high among direct patient caregivers in the acute care hospital setting; the burden is attributed, in part, to the moving, assisting, and repositioning of patients (1)(2)(3)(4). Such adverse conditions lead to substantial lost work time and restricted work duty (2,5), and they contribute to costly workers' compensation claims (6).…”
mentioning
confidence: 99%
“…A study conducted with all workers in a university hospital in North Carolina (USA) found that one-third of musculoskeletal injuries resulted from the handling of patients during the care process, including lifting, transferring, repositioning in the bed or chair, transportation in the bed or chair, and avoiding falls, among others. The highest rates of injuries were identified in hospital nurses (50%) and nursing assistants (23.1%); in turn, nursing assistants presented the highest rate of accidents (15) . Another American study pointed out that a considerable number of workers are forced to remain standing for long periods, without walking or sitting, during the work shift.…”
Section: Discussionmentioning
confidence: 98%